STRATEGI PELAYANAN ADMINISTRASI PEMERINTAH DAERAH KABUPATEN TAKALAR - Hidayanty, Dian Nur; Rahim, Samsir; Syukri, Syukri (Universitas Muhammadiyah Makassar, 2024)
This study aims to find out how to staretegi services in the national unity body and takalar district politics in order to realize effective administrative services. The number of informants in this study was 8 (eight) people. By using interview data collection techniques, observations, documentation, company documents, and literature studies. The results showed that the administrative service strategy in the national unity agency and takalar district politics can be seen from the aspects of 1) community service attributes have been said to be effective, this can be seen from the facilities and infrastructure that are sufficient, 2) aspects of the approach to improving services cannot be said to be effective, this is because employees are still slow in completing correspondence which is influenced by lack of human resources, 3) the management implementation aspect also cannot be said to be effective, this is because the training for employees in the KESBANGPOL agency in Takalar Regency is still lacking, and the 4th aspect) of the feedback system has been said to be effective, namely from the skills of the Head of the National Unity Agency and Takalar Regency Politics in understanding the obstacles experienced by the community